Patronage, Ideology and Manipulation: The Translation of Ao-men Hsin-wen-chih During the First Opium War - WANG Hai; XIAO Li (Budapest International Research and Critics University, 2019)
During the special historical period of July 1839 to November 1840, Lin Tse-hsu and his translator team selected and translated some articles from foreign newspapers such as The Canton Press,The Canton Register, The Canton Miscellany and The Chinese Repository into Chinese, which were collected intoAo-men Hsin-wen-chih(Macao News). This article explores the manipulation of patronage and ideology over the translation of Ao-men Hsin-wen-chih. As the undifferentiated patron of Ao-men Hsin-wen-chih, Lin Tse-hsu was involved in translator selection, source text selection, adding target-text annotation and he even determined and interacted with the target readers. It is also revealed that under the manipulation of patronage and ideology, the translators rewrote thetranslation by adopting such strategies as edited translation and adaptation, foreignization and domestication, uglification and dwarfing.